2022
DOI: 10.1093/noajnl/vdac010
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of T2-FLAIR mismatch sign for the IDH-mutant, 1p/19q noncodeleted low-grade glioma: An updated systematic review and meta-analysis

Abstract: Background The T2-fluid-attenuated inversion recovery (FLAIR) mismatch sign, has been considered a highly specific imaging biomarker of IDH-mutant, 1p/19q non-codeleted low grade glioma. This systematic review and meta-analysis aimed to evaluate the diagnostic performance of T2-FLAIR mismatch sign for prediction of a patient with IDH-mutant, 1p/19q non-codeleted low grade glioma, and identify the causes responsible for the heterogeneity across the included studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Although MRI features compatible with the T2FMM sign previously were included in a study of oligodendrogliomas in dogs, ours is the first study that specifically identified a significant relationship between an MRI biomarker and the oligodendroglial phenotype in dogs 18 . In adult humans, the T2FMM sign is a highly accurate biomarker for IDH1‐mutated, 1p/19q non‐codeleted astrocytomas, with specificity and sensitivity as high as 100% and 31%, respectively 8‐12 . We found a similar high specificity and low sensitivity for the T2FMM to detect oligodendrogliomas in dogs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although MRI features compatible with the T2FMM sign previously were included in a study of oligodendrogliomas in dogs, ours is the first study that specifically identified a significant relationship between an MRI biomarker and the oligodendroglial phenotype in dogs 18 . In adult humans, the T2FMM sign is a highly accurate biomarker for IDH1‐mutated, 1p/19q non‐codeleted astrocytomas, with specificity and sensitivity as high as 100% and 31%, respectively 8‐12 . We found a similar high specificity and low sensitivity for the T2FMM to detect oligodendrogliomas in dogs.…”
Section: Discussionsupporting
confidence: 66%
“…Glioma classification in humans is based on 2021 World Health Organization criteria, including genotypic, molecular and phenotypic tumor features, describing entities in which the presence of isocitrate dehydrogenase 1/2 (IDH1/2) mutations and 1p/19q codeletion status are considered important predictors of positive prognosis and longer overall survival than are found in patients carrying the wild‐type IDH1/2 gene 5‐7 . Genomic features of gliomas in humans also have been associated with certain magnetic resonance imaging (MRI) biomarkers such as the T2‐weighted (T2W)—fluid‐attenuated inversion recovery (FLAIR) mismatch (T2FMM) sign, which has high to perfect specificity and moderate to low sensitivity to predict IDH1‐mutant, 1p/19q non‐codeleted low‐grade astrocytomas (LGA) 8‐13 . The T2FMM is characterized by a homogeneous hyperintense signal on T2W and a hypointense signal with a hyperintense peripheral rim on FLAIR 8,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a metanalysis of 10 cohorts across 8 studies, a pooled specificity of 100% was reported. 3 However, the application of this imaging finding is at times questionable in clinical practice. At the initial imaging interpretation, the primary question is often not the molecular status of the glial neoplasm, but whether the observed lesion is a glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Various signs have been identified that can help to predict the molecular status of glioma in the daily clinical setting. For example, the famous T2/FLAIR mismatch signshowing low sensitivity but high specificity for IDH-mutant astrocytoma [3] has been proven to be a reliable marker. Prior to the present, differentiation and prognostic analysis of high-grade glioma from low-grade glioma were the major topics of research.…”
mentioning
confidence: 99%